Developmental fluoxetine and prenatal stress effects on serotonin, dopamine, and synaptophysin density in the PFC and hippocampus of offspring at weaning. Issue 3 (19th October 2015) - Gemmel, Mary; Rayen, Ine; Lotus, Tiffany; van Donkelaar, Eva; Steinbusch, Harry W.; De Lacalle, Sonsoles; Kokras, Nikolaos; Dalla, Christina; Pawluski, Jodi L.
ABSTRACT: Selective serotonin reuptake inhibitor medication exposure during the perinatal period can have a long term impact in adult offspring on neuroplasticity and the serotonergic system, but the impact of these medications during early development is poorly understood. The aim of this study was to determine the effects of developmental exposure to the SSRI, fluoxetine, on the serotonergic system, dopaminergic system, and synaptophysin density in the prefrontal cortex and hippocampus, as well as number of immature neurons in the dentate gyrus, in juvenile rat offspring at weaning. To model aspects of maternal depression, prenatal restraint stress was used. Sprague‐Dawley rat offspring were exposed to either prenatal stress and/or fluoxetine. Main findings show that developmental fluoxetine exposure to prenatally stressed offspring decreased 5‐HT and 5‐HIAA levels and altered the dopaminergic system in the hippocampus. Prenatal stress, regardless of fluoxetine, increased synaptophysin density in the PFC. This work indicates that early exposure to maternal stress and SSRI medication can alter brain monoamine levels and synaptophysin density in offspring at weaning. © 2015 Wiley Periodicals, Inc . Dev Psychobiol 58: 315–327, 2016.